2018
DOI: 10.1111/soc4.12626
|View full text |Cite
|
Sign up to set email alerts
|

Sociogenomics in the 21st century: An introduction to the history and potential of genetically informed social science

Abstract: This article reviews research at the intersection of genetics and sociology and provides an introduction to the current data, methods, and theories used in sociogenomic research. To accomplish this, I review behavioral genetics models, candidate gene analysis, genome-wide complex trait analysis, and the use of polygenic scores (sometimes referred to as polygenic risk scores) in the study of complex human behaviors and traits. The information provided is meant to equip readers with the necessary tools to: (1) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…The results from our study also contribute to ongoing discussions regarding sociogenomics (Braudt, 2018) and highlight the need for designs in which it is possible to disentangle purported social-genetic effects from a correlated rearing environment. In view of the pervasive evidence for passive gene–environment correlation for many behaviors (Jaffee & Price, 2007), caution is warranted when interpreting evidence for social-genetic effects.…”
Section: Discussionsupporting
confidence: 53%
“…The results from our study also contribute to ongoing discussions regarding sociogenomics (Braudt, 2018) and highlight the need for designs in which it is possible to disentangle purported social-genetic effects from a correlated rearing environment. In view of the pervasive evidence for passive gene–environment correlation for many behaviors (Jaffee & Price, 2007), caution is warranted when interpreting evidence for social-genetic effects.…”
Section: Discussionsupporting
confidence: 53%
“…Genome-wide association studies (GWAS) have discovered genetic loci associated with BMI (Locke et al, 2015;Speliotes et al, 2010;Yengo et al, 2018). Single nucleotide polymorphisms (SNPs) discovered in GWAS of BMI phenotypes have relatively small effects; therefore, polygenic scores (PGSs) have been used to combine information from multiple GWASdiscovered SNPs (Belsky & Israel, 2014;Braudt, 2018;Dudbridge, 2016). A BMI PGS focused on samples of European ancestry has been shown to be predictive of BMI, including in young adults in the United States (Belsky et al, 2012;Domingue et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Here, I argue that a genetically informed perspective provides a more complete theoretical picture of the formation of educational expectations by shedding light on processes that would not be captured in a purely phenotypic design. Behavioral genetics research has shown that there are genetic influences on virtually all human behavior (Braudt 2018;Harden and Koellinger 2020;Polderman et al 2015). According to the model of the "phenotypic bottleneck" (Freese 2008) genetic influences on distal social outcomes, such as educational expectations, are strictly mediated by embodied phenotypes, such as height, cognitive ability or personality traits (ibid.…”
Section: The Role Of Genesmentioning
confidence: 99%